Are there any changes in mothers' attitudes? Analysis of the impact of the COVID-19 quarantine on child-rearing attitudes - ÖZDEN, BÜLENT (Elsevier Ltd, 2022)
The present study aims to examine the impact of the time spent by mothers at home with their children during the quarantine period that was implemented due to the COVID-19 pandemic on the mothers’ child-rearing attitudes, taking into consideration some variables and the experiences of mothers. The study was designed using embedded mixed design, in which qualitative and quantitative research methods were used together. The quantitative research group consisted of 673 mothers and the qualitative research group consisted of 16 mothers. The research data was gathered online using the Lime Survey platform, and the interviews with the mothers were also held online. Demographic information form, the Child Rearing Attitude Scale, and a semi-structured interview form were used as data collection tools. Moderator variable analysis was used for the quantitative research data and descriptive analysis was used for the qualitative research data in support of the quantitative data. The findings revealed that the mothers’ child-rearing attitudes changed depending on the variables concerning the children; however, the quarantine period instituted due to COVID-19 had an impact on the mothers’ child-rearing attitudes depending on the variables of age and number of children. The qualitative findings obtained from the interviews supported the quantitative findings. However, it was revealed that the mothers’ attitudes towards their children underwent changes during the quarantine period under COVID-19. © 2022 Elsevier Ltd
Keywords: Child-rearing attitudes; Children; COVID-19; Mothering; Mothers' attitudes; Parenting